Direct Financing of the Religious Denominations in Spain: Changes Introduced by the 2005 General State Budget Law - Montero, Carmen Garcimartín (A journal of church and state, 2006)
Carmen Garcimartín Montero; Direct Financing of the Religious Denominations in Spain: Changes Introduced by the 2005 General State Budget Law, Journal of Church